The Current Status of Administrative and Legal Regulation of the Activities of Specially Authorized Entities in the Field of Combating Corruption in Ukraine - V. І. Strelianyi (Bulletin of Kharkiv National University of Internal Affairs)
The author has revealed the content of the term of “specially authorized entities in the field of combating corruption” contained in Part 1 of the Art. 1 of the Law of Ukraine “On Prevention of Corruption”. By analyzing the current administrative legislation of Ukraine, the range of public authorities that fall under this concept has been identified. Based on the classification of public authorities existing in administrative science, which are divided into agencies of general and special competence, the author has provided recommendations to improve the list of those public agencies that have the status of specially authorized entities in the field of combating corruption. According to the results of the study, the author has formulated an exhaustive list of specially authorized entities in the field of combating corruption in Ukraine, has provided propositions to improve the provisions of the Law of Ukraine “On Prevention of Corruption” and the Law of Ukraine “On Prosecutor’s Office” in regard to the administrative and legal status of the Specialized Anti-Corruption Prosecutor’s Office. The author has offered to amend Part 1 of the Art. 7 of the Law of Ukraine “On the Prosecutor’s Office”, supplementing it with the word “agencies” after the word “system” and before the word “prosecutor’s office”. Thus, this norm will look like this: “the system of agencies of prosecutor’s offices will consist of: 1) Attorney General’s Office; 2) prosecutor’s offices in oblasts; 3) regional prosecutor’s offices; 4) Specialized Anti-Corruption Prosecutor’s Office. It has been established that only the Specialized Anti-Corruption Prosecutor’s Office can be recognized as a specially authorized entity in the field of combating corruption among the existing prosecutor’s offices. In this regard, the application of the term of “agencies of prosecutor’s office” in Part 1 of the Art. 1 of the Law of Ukraine “On Prevention of Corruption” is not grounded and leads to a false expansion of the range of anti-corruption entities. In practice, this may lead to an ambiguous interpretation of this legal norm. In this regard, the author has offered to specify the range of prosecutorial agencies that are specially authorized entities in the field of counteraction by replacing the phrase “agencies of prosecutor’s office” with the phrase “Specialized Anti-Corruption Prosecutor’s Office”. It has been determined that either the National Police of Ukraine or its separate agencies are not specially authorized entities in the field of combating corruption. In this regard, it has been offered to amend Part 1 of the Art. 1 of the Law of Ukraine “On Prevention of Corruption” by replacing the phrase “National Police” with the phrase “National Police Units”. Thus, those structural subdivisions of the National Police agencies that exercise competence in the field of combating corruption may be recognized as specially authorized entities in the field of anti-corruption.